1962
DOI: 10.1172/jci104600
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism in Human Erythrocytes From Normal and Fava Bean-Sensitive Subjects*

Abstract: Many studies during the last decade have been concerned with the biochemical properties underlying various states of the human red blood cell, including its maturation, aging, and some abnormal conditions.A considerable amount of work has been devoted particularly to the study of erythrocyte metabolism in the fava bean-and drug-induced hemolytic anemias. Observations were first made by Beutler and his co-workers (1, 2) concerning the instability and decreased content of reduced glutathione (GSH) in red cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1963
1963
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…It is known to stimulate the hexose monophosphate shunt and to increase glucose utilization and CO2 formation; in the presence of MB, erythrocyte oxygen uptake may increase as much as twentyfold (52)(53)(54). Even in the absence of glucose, increased uptake of oxygen is observed that presumably results from utilization of intracellular phosphate esters (51); the rate of breakdown of triose phosphate is increased, and lactate is oxidized to pyruvate (53,55). Washed red cells contain almost no glucose and limited amounts of other substrates (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known to stimulate the hexose monophosphate shunt and to increase glucose utilization and CO2 formation; in the presence of MB, erythrocyte oxygen uptake may increase as much as twentyfold (52)(53)(54). Even in the absence of glucose, increased uptake of oxygen is observed that presumably results from utilization of intracellular phosphate esters (51); the rate of breakdown of triose phosphate is increased, and lactate is oxidized to pyruvate (53,55). Washed red cells contain almost no glucose and limited amounts of other substrates (56).…”
Section: Discussionmentioning
confidence: 99%
“…Not only does the hexose monophosphate shunt fail, but pentose phosphate is not returned to the glycolytic pathway from the pentose shunt (57). Fructose 6-phosphate and triose phosphate become undetectable, and glucose accumulates (53). These differences may at least partly account for the more pronounced effect of MB in inducing agglutinability of G6PD-deficient cells and the lack of a protective or ameliorative effect of added glucose.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years investigations of erythrocyte metabolism have been concerned with the interrelationships of enzymes, coenzymes, substrates, cofactors, and pH, inter alia (1)(2)(3)(4)(5)(6)(7)(8). Although data have accumulated on these various aspects of the metabolism of normal and pathological erythrocytes, little direct information has been available heretofore on pyridine nucleotide coenzymes, despite their importance in both the glycolytic and the hexose monophosphate shunt pathways.…”
mentioning
confidence: 99%
“…The glucose utilisation by intact erythrocytes was determined according to previously described procedure [2], and the reduced glutathione stability according to Beutler [3] in presence of 5 x 10-3 M glucose.…”
Section: Methodsmentioning
confidence: 99%